Border Disputes and Its Impact on Bilateral Relation: A Case of Nepal- India International Border Management - Baral, Toya Nath (Journal of APF Command and Staff College, 2018)
This paper examines the historical events of Nepal-India international boundary. How the delineation and demarcation of international boundary was carried out, is strategically explained. Border water issues are raised. Encroachments and disputes due to river boundary are also discussed. Disputes on both Physical and artificial boundary and their impacts on bilateral relation is analyzed. Both positive and negative impact of an open border system between Nepal and India is discussed. Border problems are identified clearly. Initiatives taken how to resolve the border management issues are categorically presented. Strip mapping of boundary area was carried out using GPS and GIS technology and the maps of whole Nepal-India boundary, except Kalapani and Susta, are prepared jointly and signed by the joint technical committee assigned by the respective government.